Profiles and spatial distributions of heavy metals, microbial communities, and metal resistance genes in sediments from an urban river - Fu, Lingfang; Yu, Yang; Yu, Fei; Xiao, Jieer; Fang, Huaiyang; Li, Weijie; Xie, Zhijie; Zhang, Feng; Lin, Shu (Frontiers in Microbiology, 2023)
The occurrence and propagate of resistance genes under influence from heavy metals in the river has become an emerging environmental issue. Little is known about the co-occurrence of microbial community and resistance genes in river sediment under low heavy metals (HMs) contaminants. In this study, the profiles and spatial distribution of HMs, microbial community, and metal resistance genes (MRGs) were analyzed via collected sediment samples from the Zhilong River basin in Yangjiang city, the neighboring cities in the Pearl River Delta. The results indicated the concentrations of heavy metals of copper (Cu), cadmium (Cd), lead (Pb), chromium (Cr), nickel (Ni) in this study were at the relatively low levels compared with those of river sediments in China. The composition of HMs chemical fractions and structure of microbial community obviously variated along mainstream, but composition of MRG abundance was relatively homogeneous in mainline sediments, which indicated that there were significant spatial distribution differences in low HMs pollution area. Moreover, the variation of HMs and microbial community in up-midstream was distinctly discerned from tributaries, and the input of which as main external immigration was one of major factor to affect the HMs chemical fractions and genera structure in mainstream. The relationship analysis indicated that there was no significant congruence between HMs, bacterial community, and MRGs profile, and the heavy metal was not the main factor to derive the metal resistance genes (MRGs) in sediments. The result obtained here could be benefited to understand the propagating of heavy metals resistance genes in urban river in developing city.